Implementasi Kebijakan Pelayanan Informasi dan Dokumentasi dalam Meningkatkan Pelayanan Humas pada BPSDM Provinsi Sumatera Utara - Dewi Trisnawati; Budi Hartono; Dumasari Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The objectives to be achieved are to know and analyze about: Implementation of Information and documentation service policies in improving Public Relations Services at the Human Resources Development Agency of North Sumatra Province and what factors support and hinder it. . This research uses a type of qualitative research that focuses on the Implementation of Information and Documentation Service Policies in Improving Public Relations Services at the Human Resources Development Agency by focusing on the flow of services and personnel willingness and competence in providing information and documentation for the public. In the framework of the Implementation of Information and Documentation Services in Improving Public Relations Services, it becomes a supporting element for BPSDM Nort Sumatra Province in carrying out its activities as a training institution that creates Professional, Trustworthy and Dignified ASN. Implementation at the Human Resource Development Board of North Sumatra Province needs overall support and commitment to get better results. This is demonstrated by the leadership's commitment to improving the performance and competence of personnel in managing information and documentation in improving public relations services. The inhibiting factors in terms of communication, resources, disposition and bureaucratic structure make it a consideration for BPSDM Nort Sumatra Province to continue to strive to implement personnel performance and competence improvement programs in managing Information and Documentation in Improving Public Relations Services through collaborative planning, budgeting, implementation, evaluation and reporting as a whole.